INOVASI PEMBELAJARAN DI MADRASAH: PENGENALAN DEEP LEARNING DAN PENYUSUNAN RPP DENGAN BANTUAN AI - Yunitari Mustikawati; Andi Hajar; Lely Novia; Nurdin Noni; Fitri Radhiyani (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
Education in Madrasah faces the challenge of developing learning methods that are in line with the needs of the 21st century, especially with the rapid development of technology. Deep Learning and Artificial Intelligence (AI) enable deeper understanding and relevant applications to improve the quality of teaching. The purpose of this service activity is to introduce the use of AI such as ChatGPT and Microsoft Copilot to create more efficient lesson plans, as well as interactive applications such as Canva and Heyzine to create engaging teaching materials. The methods used are workshop-based training and direct simulations. The results of the training showed a significant ability of teachers to use technology in creating lesson plans with a Deep Learning approach and utilizing AI in preparing lesson plans as well as using Canva and Heyzine technology in interactive teaching materials.